2015
DOI: 10.1038/modpathol.2015.64
|View full text |Cite|
|
Sign up to set email alerts
|

Mammary analog secretory carcinoma, low-grade salivary duct carcinoma, and mimickers: a comparative study

Abstract: Mammary analog secretory carcinoma (MASC) is a recently recognized low-grade salivary carcinoma characterized by a specific ETV6 rearrangement. We describe 14 new MASCs and examine their immunophenotypic and genetic profiles in the context of look-alikes, namely, low-and high-grade salivary duct carcinoma and acinic cell carcinoma. ETV6 rearrangement, and robust expression of mammaglobin and S100, were demonstrated in 11/11, 14/14, and 12/14 MASCs, respectively. All low-grade salivary duct carcinomas coexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 42 publications
8
95
0
Order By: Relevance
“…Notably, multiple authors have described some patterns found in MASC as appearing similar to thyroid colloid-like deposition or a follicular pattern of thyroid carcinoma [1,3,7,17]. Nuclear features of our patient's tumor also resembled closely those of PTC in that the nuclei were vesicular with numerous nuclear grooves.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Notably, multiple authors have described some patterns found in MASC as appearing similar to thyroid colloid-like deposition or a follicular pattern of thyroid carcinoma [1,3,7,17]. Nuclear features of our patient's tumor also resembled closely those of PTC in that the nuclei were vesicular with numerous nuclear grooves.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, one case of mammary analog secretory carcinoma has been reported as arising in (or near) the thyroid gland [7]. Our report details a second patient with mammary analog secretory carcinoma apparently arising in the thyroid with diagnosis confirmed on PCR for an ETV6-NTRK3 fusion and with characteristic immunohistochemical features.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations